Hippocampal long-term depression in anaesthetised adult rats: Involvement of glutamate and acetylcholine receptors - O'RIORDAN, KENNETH JOSEPH (Trinity College Dublin. School of Medicine. Discipline of Pharmacology & Therapeutics, 2017)
Abstract: Hippocampal long-term depression in anaesthetised adult rats: Involvement of glutamate and acetylcholine receptors Kenneth J. O?Riordan Department of Pharmacology and Therapeutics School of Medicine, University of Dublin, Trinity College Synaptic long-term depression (LTD) is believed to underlie critical mnemonic processes in the hippocampus. Elucidation of the mechanisms of LTD may provide a means of understanding synaptic plasticity processes that are believed to underlie information storage in learning and memory, as well as memory dysfunction, such as occurs in early Alzheimer?s disease (AD). In the work presented here, the mechanisms underlying the induction of synaptic LTD in the adult rat dorsal hippocampus in vivo, using different pathways of synaptic activation and pharmacological challenges, were examined. Induction of LTD in the intact hippocampus of adult animals has proven difficult to achieve; thus, most research on this topic has been performed in hippocampal slices from young animals mainly using electric field stimulation of mixed pathways en masse. The recent development of the technique of optogenetics using virally directed expression of a light-activatable trans-membrane ion channel in the hippocampus, promises high temporal precision of synaptic activation, high spatial resolution and a very selective means to study isolated network synaptic plasticity. We compared electrically and optogenetically induced LTD at CA3-to-CA1 apical synapses in urethane anaesthetised rats. We confirmed that the expression of Channelrhodopsin 2 (ChR2-eYFP), was specifically, but relatively diffusely expressed in CA3 pyramidal neurons originating at the site of injection, thereby allowing relatively selective excitation of either Schaffer collaterals or commissural fibres, avoiding stimulation of en passant cholinergic neurons and decreasing the likelihood of peri/extra-synaptic glutamate receptor activation. LTD induction at apical CA1 synapses has been divided into NMDA receptor (NMDAR) and metabotropic glutamate receptor (mGluR) ?dependent forms. Seeing that electrical stimulation is likely to co-activate both perisynaptic mGlu5R and nearby NMDARs, we examined their potential interaction during the induction of LTD by low-frequency stimulation (LFS, 900 pulses of high-intensity pulses at 1 Hz). We found evidence that although LTD induction with electrical LFS of Schaffer collateral/ commissural inputs was primarily dependent on NMDARs, it was also facilitated by endogenously released glutamate-mediated activation of mGlu5Rs. This LTD was only blocked by high local doses of NMDAR antagonists when tested alone and was dependent on GluN2B-subunit-containing NMDARs as well as the NMDAR ion channel function. In contrast, LTD induction by optical LFS excitation of CA3 Schaffer collaterals, induced a similar magnitude, input-specific LTD that was also NMDAR-dependent but not modulated by mGlu5R. Whereas selective activation by a highly potent mGlu5R positive allosteric modulator showed no effect on a weak optical stimulation LFS (1Hz, 300 or 600 pulses), it strongly enhanced LTD induction by a weak electrical LFS. Moreover, LTD induction by oLFS was potently blocked by systemic treatment with selective inhibitors of the ion channel and GluN2B subunit of NMDARs. Previously our laboratory had reported that electrical LFS-induced LTD was muscarinic acetylcholine receptor-dependent (mAChR). We revisited the involvement of cholinergic transmission, utilising optogenetics to avoid directly activating cholinergic input during LFS. A mAChR antagonist that abrogated electrically induced LTD did not significantly affect optical induction of LTD. Moreover, pharmacologically boosting endogenous ACh levels lowered the threshold for the induction of LTD by a weak electrical conditioning protocol, yet had no discernible effect on the ability to induce LTD by optical LFS that was either peri-threshold or submaximal. Finally, we re-examined the role of NMDARs in the ability of synthetic synaptotoxic aggregates of human Aβ1-42 (amyloid-β derived diffusible ligands - ADDLs) to enhance electrically induced LTD and found evidence that it required NMDARs that contain the GluN2B subunit. Furthermore, ADDLs effected a modest facilitation of LTD induced by a weak optical LFS protocol (1Hz, 300 pulses), which appeared to be lateralised: Aβ preferentially facilitated the induction of optically induced LTD at Schaffer collaterals in the left hippocampus. The present findings provide strong evidence in the living animal that electrical LFS of Schaffer collateral/ commissural fibres triggers an NMDAR-dependent LTD that is strongly modulated by mGlu5R and mAChR co-activation. In contrast, selective optical LFS of CA3 pyramidal neurons expressing ChR2 induced robust NMDAR-dependent LTD that was relatively independent of mGlu5R and cholinergic input. The GluN2B subunit and ion channel function mediated the NMDAR-dependence of both forms of LTD. Moreover, both forms of LTD were blocked by a protein synthesis inhibitor, indicating a critical need for new protein synthesis similar to long-term memory consolidation. The data also revealed a role for NMDARs and lateralisation in the facilitation of LTD by Aβ.
APPROVED